Specific and reproducible gas sensors utilizing gas-phase chemical reaction on organic transistors - Zang, Yaping (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.